Association between Polymorphism of β-Lactoglobulin Gene on Milk Yield and Quality in Local Sheep at Jonggol Animal Science Teaching and Research Unit (JASTRU) - Sumantri, Cece; Nurhayati, Nurhayati D.; Farajallah, Ahmad; Anggraeni, A. Anggraeni (BRIN, 2008)
The aims of this study were to identify the effects of polymorphism of b-lactoglobulin gene on milk yield and percentage of milk protein and fat in local sheep. A total number of 83 heads of lactating ewes raised under an extensive management at Jonggol Animal Science Teaching and Research Unit (JASTRU) of the Faculty of Animal Science, Bogor Agricultural University were studied. Research activities were carried out through some steps involving blood collection. DNA isolation, DNA amplification, and separation of DNA fragments by electrophoresis with silver staining method. By using polymerase chain reaction (PCR) then genotyped by single strand conformation polymorphism technique (SSCP), it was successfully amplified a fragment length at 420 bp in b-lactoglobulin genelocated on the exon 7. The electrophoresis pattern revealed 5 types of b-lactoglobulin gene and designated as A, B, C, D, and E types. The proportion for those respective 5 type from the highest to the lowest were for A (27.71%), C (16.87%), D (12.05%), E (10.84%), and B (9.64%), respectively. There were no significant effect of polymorphisms in b-lactoglobulin gene on both milk yield and quality in local sheep at JASTRU.